Comparative Study of Antimicrobial Efficacy of Honey, Clove, and Ginger Extracts against Some Bacteria Isolated from Tiger Nut Milk - Olofu, Victor A.; Adeshina, Gbonjubola O.; Olayinka, B. O.; Mshelia, Mari B. (PSM Microbiology, 2025)
Tiger nut milk (kunun aya) is a popular traditional beverage in Nigeria but is often contaminated due to unhygienic processing and handling, posing a food safety risk. This study evaluated the antimicrobial activity of honey, and aqueous and ethanolic extracts of clove (Syzygium aromaticum) and ginger (Zingiber officinale) against bacteria isolated from tiger nut milk sold in Zaria, Nigeria. A total of nine bacterial isolates—Escherichia coli, Mannheimia haemolytica, Hafnia alvei, Staphylococcus aureus, Burkholderia cepacia, Micrococcus spp., Bacillus spp., Stenotrophomonas maltophilia, and Citrobacter freundii—were tested using agar well diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) assays. Results showed concentration-dependent inhibition by honey, clove, and ginger extracts. Honey at 90% v/v exhibited notable activity, particularly against M. haemolytica. Ethanolic clove extract produced the strongest inhibition zones (up to 28 mm) and lower MIC values compared to its aqueous equivalent, while ethanolic ginger showed stronger effects than aqueous ginger, though differences were not statistically significant. The findings highlight that ethanolic clove extract and high-concentration honey possess promising antibacterial activity and could serve as affordable, natural preservatives to enhance the safety of tiger nut milk. Further research is recommended to standardize extract formulations and assess their effectiveness under real storage and vending conditions.